Remote conferences in parasitology and entomology during the pandemic: Eliminate or maintain in a post-pandemic world? That is the dilemma! - Genta, Fernando Ariel (2023)
The COVID-19 pandemic brought enormous challenges for health, scientists and academic world two years ago. Social isolation and the inabilities of face-to-face activities generated the emergence of many educational and scientific initiatives. Remote activities gave information and brought company and affection to people which allowed students and professionals from different parts of the world to integrate. In this report we are showing the experience from three initiatives in South America of scientific dissemination in infectious diseases. We discuss the scope of having a permanent practice for access and integration in science using remote communication, which can give great benefits in unequal societies.